Fitness and Health Android Mobile Application for UNIMAS student - Simon, Jau (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The purpose of the FitUNIMAS mobile Android application project is to tackle the rising of health problem among student. This project is aimed specifically at UNIMAS student. Health is one of the most important aspect in our life. Ignoring our health can only bring many health problems later in life. The rising of health problems among adolescence aged from 18 above is concerning. To develop the application, the methodology used is Waterfall Model due to time restriction and direct flow of works. To gather requirements, literature review of existing systems been done alongside questionnaire. The information gathered are analyze and UML diagrams with wireframe of the application are constructed to assist the development of the project. In the end of the development, an Android mobile application named FitUNIMAS will be designed, programmed and ready to be deployed to use by UNIMAS student.